Chapter Con chi vengo vengo di Michele della Marra fra Calderón e Angiola D'Orso - CAPPELLI, FEDERICA (Studi e saggi, 2020)
This paper aims at studying the Italian fortune of the Calderonian play Con quien vengo vengo , firstly, by focusing on its first version by Michele della Marra (1665) and then moving on to a triple textual comparison between the Calderonian source-text, the rewriting of Della Marra and the second adaptation by the actress Angiola D'Orso, whose first edition came out in 1666. Despite his faithfullness to the plot of the original text, the first translator remodels the text either by summarizing it, or removing certain typically Calderonian rhetorical artifices, or replacing the figure of the gracioso by that of the southern servant, who uses the dialect. On the contrary, Angiola D'Orso shows greater respect for the Spanish play, displaying more sensitiveness toward its rethorical beauty, which she is able to reproduce successfully.